1315. Dental Discoloration and Enamel dysplasia after Tetracyclines Exposure in Children: A Nationwide Population-Based Study in Korea. (15th December 2022) - Lee, Ji Young; Kim, Eun Hwa; Lee, Myeongjee; Shin, Je Hee; Lim, Sung Min; Jung, In Kyung; Ahn, Jong Gyun; Kang, Chung-Min; Kang, Ji-Man
Abstract: Background: Tetracycline (TC) is not recommended for pediatric use due to the risk of permanent teeth discoloration and enamel dysplasia. We aimed to assess the incidence of dental abnormality in Korean children and investigate whether the risk was greater in tetracycline-exposed children compared to the general population. Methods: This nationwide, population-based study using Health Insurance Review and Assessment service database included children (aged 0-12 years) who were prescribed tetracycline for at least a day between January 2008 and December 2020. We evaluated the incidence rate of children who were inserted diagnosis codes for dental discoloration and enamel dysplasia after at least 6 months after prescription as the primary outcome. Standardized incidence ratio was analyzed to determine whether the risk of dental abnormalities was greater in the exposed group compared to the general population in Korea. Results: A total of 56, 990 patients with TCs exposure were included, 3% were under the age of 8 (n=1, 735) while the majority of 97% were between ages of 8 and 12 (n=55, 255). The incidence rate in 0-7 year old age group was 734 cases per 100, 000 person-years, which was about five times higher than the 143 cases per 100, 000 person-years of the 8-12 year old group with statistical significance ( P < 0.001). The 5-year cumulative incidence rate in the 0-7 years old age group was 4.1 % (95% CI, 3.0-5.7%) and 5.7% (95% CI, 4.1–7.8%) in 10-year period. In the 8-12 year old age group, 5-year cumulative incidence was 0.8% (95% CI, 0.7-0.9%) and 1.3% (95% CI, 1.1-1.4%). The risk of dental abnormalities was not significantly increased in the TC-exposed group of 0-7 year old age group compared to the general population (SIR = 1.08; 95% CI, 0.69-1.60). Conclusion: The incidence of tooth discoloration and enamel dysplasia was lower than previously suggested, particularly between the ages of 8 and 12 and as low as one-fifth of those under the age of 8, suggesting a reconsideration of limiting use of TCs in children if clinically indicated. Disclosures: All Authors : No reported disclosures.